HUBUNGAN PERILAKU IBU HAMIL DAN MOTIVASI PETUGAS KESEHATAN DENGAN KEPATUHAN DALAM MENGKONSUMSI TABLET ZAT BESI DI KLINIK BERSALIN ROMANA TAHUN 2016 - Anita Veronika Barus; Bernadetta Ambarita (Elisabeth Health Jurnal, 2016)
Iron nutritional anemia may increase the risk of complications and deaths in pregnancy and childbirth in the event of excessive bleeding. Most likely the cause is pregnant women who do not consume iron tablets. Iron nutritional anemia is one of the main nutritional problems in Indonesia where the mortality rate in pregnant women is still quite high. To overcome these problems, the government implemented a program of giving iron tablets to pregnant women. Goals : This research was conducted in Romana Maternity Clinic which aims to know the relationship between pregnant women behavior and the motivation of health officer with compliance to consume iron tablets in pregnant women. Methods : The type of this research is descriptive analytic survey research using questionnaire as an interview guide. The population in this study were all pregnant women (sekundigravida and multigravida) who checked her pregnancy at Romana Maternity Clinic. The entire population becomes the object of research. Result : The results showed that 72% of obedient pregnant women consumed iron tablets and 28% did not comply. From result of data analysis using chi-square found that knowledge of pregnant mother correlated significantly with compliance to consume iron tablet, while result of exact fisher data analysis obtained by attitude of pregnant mother, pregnant woman action and motivation of health officer not related significantly with compliance consuming tablet substance iron. Conclution : It is recommended that the knowledge of the community, especially pregnant women about the importance of iron tablets is further enhanced as well as health workers to improve IEC (Communication, Information and Education) to pregnant women who check their pregnancy at puskesmas to overcome iron nutrition anemia.